THE INFLUENCE OF SOCIAL MEDIA MARKETING ON BRAND SATISFACTION AND BRAND LOYALTY OF WARDAH BRAND COSMETIC PRODUCTS WITH CUSTOMER BRAND ENGAGEMENT AS A MEDIATION VARIABLE ON THE INSTAGRAM PLATFORM - Nurul Azmi; Mariyudi; Adnan; Naufal Bachri; Ikramuddin; Sapna Biby (CV. Radja Publika, 2026)
The purpose of this study is to examine the influence of social media marketing on brand satisfaction and brand loyalty of Wardah cosmetic products with customer brand engagement as a mediating variable on the Instagram platform. The data in this study were 165 consumers of Wardah cosmetic products. Data collection in this study used a questionnaire with data analysis tools using Structural Equation Modeling (SEM) operated by the Amos device. The results of the study indicate that social media marketing has a positive and significant effect on customer brand engagement, customer brand satisfaction, and brand loyalty. Then, customer brand engagement has a positive and significant effect on customer brand satisfaction and brand loyalty. And the mediation effect test found that customer brand engagement is a partial mediating variable between social media marketing and brand satisfaction and brand loyalty. The results of this study are expected to provide important contributions for stakeholders in developing cosmetic product marketing strategies and customer understanding of products and brands.